HUBUNGAN DAYA LEDAK OTOT TUNGKAI DAN KELENTUKAN PERGELANGAN TANGAN TERHADAP HASIL SMASH PADA TIM BOLA VOLI PUTRI SMAN OLAHRAGA RIAU - Afrilia, Rosi; Ramadi, Ramadi; Vai, Aref (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The problem in this research is the smash skill is still not good, it is seen when the athlete smash, the ball often does not pass the net and do not find the right target and do not generate points for the team. This is due to lack of reach when the athlete to smash because the wrist muscle and explosive muscular tungkainya not maximal .. This study aims to determine whether there is an explosion of muscle limb power and the elaboration of the wrist with smash results on the team volleyball daughter SMAN Sports Riau. This type of research is Correlation to see the level of relationship of different variables. Sampling technique is the total population (total sampling) athlete Ball volleyball SMAN Sports Riau, the sample in this study is athletes daughter Volleyball SMAN Sports Riau amounted to 18 people. The research was conducted at Gor Volleyball SMAN Sports Riau. Instrument used in this research is Vertical Jump Test, Test of Wrist Hands and Spike Test. The result of data in this research is smash. The analysis is done using multiple correlation. Based on data analysis and discussion, proven with Thitung of 0,604 and Ttabel 0,482. Means Thitung> Ttabel.Pada level ɑ = 0.05. Then it can be concluded that there is a relationship of explosive muscle limb power and the elaboration of wrist with smash results on the team volleyball daughter SMAN Sports RiauKey Words: Explosive Muscle Limb Power, Elasticity, Smash.